WHAT IS “RIGHT” IN TRANSLATION: CROSS-CULTURAL DIFFERENCES FROM LINGUISTIC POINT OF VIEW - Markuckaitė, EGLĖ; Grigaliūnienė, Jonė (Vertimo studijos, 2017)
[full article, abstract in English; abstract in Lithuanian]The present paper reports on the study of the cultural word right, which is arguably one of the most culture-specific words in the English language (Wierzbicka 2006, 64). One of the means of measurement of culture-specificity is its translation into other languages. In the present study, the Parallel English-Lithuanian Corpus, compiled at the Centre of Computational Linguistics of Vytautas Magnus University, was used as the basis for checking the translations of the word right. Both quantitative and qualitative methods of research were applied in distinguishing the senses of the English word right and its correspondences in Lithuanian as well as making some inferences regarding the possible cultural differences. The research findings show that while the concept of the English word right is based on respect for rational thinking, logical deductions, and evidence, the Lithuanian correspondences are associated more with metaphysical truth and the dichotomy between GOOD and BAD.